Recommendations for screening and early detection of common cancers in India. Issue 7 (July 2015) - Rajaraman, Preetha; Anderson, Benjamin O; Basu, Partha; Belinson, Jerome L; Cruz, Anil D'; Dhillon, Preet K; Gupta, Prakash; Jawahar, Tenkasi S; Joshi, Niranjan; Kailash, Uma; Kapambwe, Sharon; Katoch, Vishwa Mohan; et al.
Summary Cancers of the breast, uterine cervix, and lip or oral cavity are three of the most common malignancies in India. Together, they account for about 34% of more than 1 million individuals diagnosed with cancer in India each year. At each of these cancer sites, tumours are detectable at early stages when they are most likely to be cured with standard treatment protocols. Recognising the key role that effective early detection and screening programmes could have in reducing the cancer burden, the Indian Institute for Cytology and Preventive Oncology, in collaboration with the US National Cancer Institute Center for Global Health, held a workshop to summarise feasible options and relevant evidence for screening and early detection of common cancers in India. The evidence-based recommendations provided in this Review are intended to act as a guide for policy makers, clinicians, and public health practitioners who are developing and implementing strategies in cancer control for the three most common cancers in India.